Comparative transcriptome analysis reveals resistance-related genes and pathways in Musa acuminata banana 'Guijiao9' in response to Fusarium wilt - Sun, J.; Zhang, J.; Fang, H.; Peng, L.; Wei, S.; Li, C.; Zheng, S.; Lu, J. (Elsevier, 2019)
Fusarium wilt caused by Fusarium oxysporum f. sp. cubense (Foc), is one of the most devastating diseases in bananas resulting in significant loss of Cavendish bananas production worldwide. Here we show the agronomic traits and the resistance of 'Guijiao 9' in the field trials from 2012 to 2017. And then we dissect and compare the transcriptome response from these two cultivars (cv. 'Guijiao 9' and cv. Williams) in an attempt to understand the molecular basis that contribute to the enhanced Foc tropical race 4 (Foc-TR4) resistance. 'Guijiao 9' is a Cavendish cultivar with strong resistance to Foc-TR4, which was reflected in a lower disease severity and incidence in glasshouse and field trails, when compared to the susceptible cultivar Williams. Gene expression profiles of 'Guijiao 9' and Williams were captured by performing RNA-Seq analysis on 16 biological samples collected over a six day period post inoculation with Foc-TR4. Transcriptional reprogramming in response to Foc-TR4 was detected in both genotypes but the response was more drastic in 'Guijiao 9' than in Williams. Specific genes involved in plant-pathogen interaction and defense signaling including MAPK, calcium, salicylic acid, jasmonic acid and ethylene pathways were analyzed and compared between 'Guijiao 9' and Williams. Genes associated with defense-related metabolites synthesis such as NB-LRR proteins, calmodulin-binding protein and phenylpropanoids biosynthesis genes were significantly up-regulated in 'Guijiao 9' resistant to Foc-TR4 infection. Taken together, this study highlights the important roles of plant hormone regulation and defense gene activation in mediating resistance in 'Guijiao 9'.